Contemporary Management of Borderline Resectable and Locally Advanced Unresectable Pancreatic Cancer. (1st February 2016) - Shaib, Walid L.; Ip, Andrew; Cardona, Kenneth; Alese, Olatunji B.; Maithel, Shishir K.; Kooby, David; Landry, Jerome; El-Rayes, Bassel F.
Abstract: Adenocarcinoma of the pancreas remains a highly lethal disease, with less than 5% survival at 5 years. Borderline resectable pancreatic cancer (BRPC) and locally advanced unresectable pancreatic cancer (LAPC) account for approximately 30% of newly diagnosed cases of PC. The objective of BRPC therapy is to downstage the tumor to allow resection; the objective of LAPC therapy is to control disease and improve survival. There is no consensus on the definitions of BRPC and LAPC, which leads to major limitations in designing clinical trials and evaluating their results. A multimodality approach is always needed to ensure proper utilization and timing of chemotherapy, radiation, and surgery in the management of this disease. Combination chemotherapy regimens (5-fluorouracil, leucovorin, irinotecan, oxaliplatin, and gemcitabine [FOLFIRINOX] and gemcitabine/nab-paclitaxel) have improved overall survival in metastatic disease. The role of combination chemotherapy regimens in BRPC and LAPC is an area of active investigation. There is no consensus on the dose, modality, and role of radiation therapy in the treatment of BRPC and LAPC. This article reviews the literature and highlights the areas of controversy regarding management of BRPC and LAPC. Abstract : This article reviews the literature and highlights the areas of controversy regarding management of borderline resectable pancreatic cancer (BRPC) and locally advanced unresectable pancreatic cancer (LAPC). The lack of consensus on the definitions of BRPC and LAPC leads to major limitations in designing clinical trials and evaluating their results. The role of combination chemotherapy regimens, which have improved overall survival in metastatic disease, is an area of active investigation.